p53 isoform expression promotes a stemness phenotype and inhibits doxorubicin sensitivity in breast cancer - Luiza Steffens Reinhardt; Kira Groen; Xiajie Zhang; Brianna C. Morten; Anna Wawruszak; Kelly A. Avery-Kiejda (Cell Death and Disease, 2023)
Abstract In breast cancer, dysregulated TP53 expression signatures are a better predictor of chemotherapy response and survival outcomes than TP53 mutations. Our previous studies have shown that high levels of Δ40p53 are associated with worse disease-free survival and disruption of p53-induced DNA damage response in breast cancers. Here, we further investigated the in vitro and in vivo implications of Δ40p53 expression in breast cancer. We have shown that genes associated with cell differentiation are downregulated while those associated with stem cell regulation are upregulated in invasive ductal carcinomas expressing high levels of Δ40p53. In contrast to p53, endogenous ∆40p53 co-localised with the stem cell markers Sox2, Oct4, and Nanog in MCF-7 and ZR75-1 cell lines. ∆40p53 and Sox2 co-localisation was also detected in breast cancer specimens. Further, in cells expressing a high ∆40p53:p53 ratio, increased expression of stem cell markers, greater mammosphere and colony formation capacities, and downregulation of miR-145 and miR-200 (p53-target microRNAs that repress stemness) were observed compared to the control subline. In vivo, a high ∆40p53:p53 ratio led to increased tumour growth, Ki67 and Sox2 expression, and blood microvessel areas in the vehicle-treated mice. High expression of ∆40p53 also reduced tumour sensitivity to doxorubicin compared to control tumours. Enhanced therapeutic efficacy of doxorubicin was observed when transiently targeting Δ40p53 or when treating cells with OTSSP167 with concomitant chemotherapy. Taken together, high Δ40p53 levels induce tumour growth and may promote chemoresistance by inducing a stemness phenotype in breast cancer; thus, targeting Δ40p53 in tumours that have a high Δ40p53:p53 ratio could enhance the efficacy of standard-of-care therapies such as doxorubicin.